The soft edge : - Karlgaard, Richard (Jossey-Bass, 2014)
What does it take to get ahead now--and stay there? High performance has always required shrewd strategy and superb execution. These factors remain critical, especially given today's unprecedented business climate. But Rich Karlgaard--Forbes publisher, entrepreneur, investor, and board director--takes a surprising turn and argues that there is now a third element that's required for competitive advantage. It fosters innovation, it accelerates strategy and execution, and it cannot be copied or bought. It is found in a perhaps surprising place--your company's values. Karlgaard examined a variety of enduring companies and found that they have one thing in common; all have leveraged their deepest values alongside strategy and execution, allowing them to fuel growth as well as weather hard times.